Hypertrophic Osteodystrophy in a Toy Breed - Appeldoorn, A.-M.; Schrauwen, E. M. J. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Hypertrophic osteodystrophy, a developmental disease that primarily affects immature dogs of large breeds, was diagnosed in a four-months-old Maltese puppy. It was treated with a change in diet, but additional therapy with corticosteroids was temporarily required, due to an explosive periosteal new bone formation.
Keywords: Hypertrophic osteodystrophy; toy breed dog